Foot Morphological Adaptations Developed After Eight Weeks of Barefoot Running Training [Modificaciones Morfológicas del Pie Luego de Ocho Semanas de Entrenamiento de Carrera a Pie Descalzo] - Sanchez-Ramirez, C (Universidad de la Frontera, 2019)
Barefoot runni ng has been st udi ed extensively recently, but little is known of the anatomical changes that take place in the foot. The objective of this study was to determine the acute and chronic changes that are produced in subjects who train barefoot. 29 subjects divided into two groups, Barefoot (BFGr) (n=17) and Shod (SGr) (n=12), followed an acute effect protocol which consisted in running during 20 min on a treadmill at 3.1 m/s, and an eight-week long chronic effect protocol covering eight weeks of resistance running with progressively increasing volume. BFGr did all the sessions barefoot. At the end of each protocol Foot Length (FL), Forefoot Width (FW), Hindfoot Width (HW), Navicular Height (NH), Arch Index (AI), and Maximum Surface (MS) were measured. ANOVA 3x2 was run to verify the effects caused by time and the shod condition produced. Shod/ Unshod factor caused significant effects on all the variables (FL: p=0.000, η2p=0.997; FW: p=0.000, η2p=0,997; HW: p=0.000, η2p= 0,994; NH: p=0.000, η2p=0.953; AI: p=0.000, η2 p=0.898; MS: p=0.000, η2 p=0.983), and the time factor on AI (p=0.012, η2p=0.152) and MS (p=0.000, η2p=0.259). There was a significant Time x Condition interaction in FW (p=0.036, η2p=0.116) and NH (p=0.019, η2 p= 0.143). MS increased after the acute (p=0.000) and the chronic (p=0.001) protocols in the BFGr. The percentage of subjects with normal feet increased in the BFGr and that with flat feet increased in SGr. Barefoot running training causes effects, mainly after an adaptation period of eight weeks, tending to a harmonic surface increase on the support plantar area, with a relative decrease of the midfoot area, which meant a decrease of subjects with plantar arch of flat type. © 2019, Universidad de la Frontera. All rights reserved.
Keywords: Barefoot; Running; Foot; Flatfoot; Morphology; Plantar Pressure